Review of the monograph “Transport Terminals” - Žiliukas, Antanas (Transport, 2002)
The monograph is intended to deal with the topical issues of transport terminal technological processes and their management. The authors present their systemised theoretical solutions and indicate the spheres of their application.First Published Online: 19 Dec 2011